2013
DOI: 10.1007/s00284-013-0369-7
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution of Ammonia-Oxidizing Archaea and Bacteria in Sediments of a Eutrophic Lake

Abstract: In order to characterize the vertical variation of abundance and community composition of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) in sediments of a eutrophic lake, Lake Taihu, molecular techniques including real-time PCR, clone library, and sequencing were carried out in this study. Abundances of archaeal amoA gene (ranged from 2.34 × 10(6) to 4.43 × 10(7) copies [g dry sediment](-1)) were higher than those of bacterial amoA gene (ranged from 5.02 × 10(4) to 6.91 × 10(6) copies [g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…AOA and AOB diversity and abundance in the sediments of Beiyun River Diversity estimates based on clone libraries of amoA genes in this study were within the same range of that in the sediments of estuaries (Wankel et al 2011;Zheng et al 2013;Chen et al 2014) and freshwater lakes (Liu et al 2015), while these indices were generally higher than that reported in the sediments of eutrophic lake (Zeng et al 2012;Zhao et al 2013Zhao et al , 2014. Archaeal amoA sequences from the eight samples showed higher Shannon diversity than bacterial amoA, which was in agreement with the results in previous studies Zheng et al 2013).…”
Section: Discussionsupporting
confidence: 91%
“…AOA and AOB diversity and abundance in the sediments of Beiyun River Diversity estimates based on clone libraries of amoA genes in this study were within the same range of that in the sediments of estuaries (Wankel et al 2011;Zheng et al 2013;Chen et al 2014) and freshwater lakes (Liu et al 2015), while these indices were generally higher than that reported in the sediments of eutrophic lake (Zeng et al 2012;Zhao et al 2013Zhao et al , 2014. Archaeal amoA sequences from the eight samples showed higher Shannon diversity than bacterial amoA, which was in agreement with the results in previous studies Zheng et al 2013).…”
Section: Discussionsupporting
confidence: 91%
“…The important roles of sediment microbes in energy and matter transformation in aquatic environments have been reported previously (Boyle-Yarwood et al 2008;Glissman et al 2004;Schmalenberger et al 2008;Tamaki et al 2005). Some studies about the sediment microbes have been performed on the functional microorganisms, such as the methanogens (Antony et al 2012), the Miscellaneous Crenarchaeotic Group , and the ammoniaoxidizing bacteria (Zhao et al 2013). Others dealt with the diversity shift of microorganisms against the changes of environment factors (Blöthe et al 2008;Hoostal and Bouzat 2008;Wang et al 2011), and also the spatial and temporal variations of sediment bacteria (Bai et al 2012 Nam et al 2008;Qu et al 2008;Szabó et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The distribution of sediment ammonia-oxidizing archaeal and bacterial populations has been investigated in a variety of freshwater ecosystems, such as river (Reis et al 2015;Sonthiphand et al 2013;Sun et al 2013;Xie et al 2014), reservoir , lake (Bollmann et al 2014;Hou et al 2013;Liu et al 2015;Mukherjee et al 2016;Zhao et al 2013Zhao et al , 2014, wetland (Liu et al 2014a;Wang et al 2013;Yang et al 2014), and pond (Lu et al 2015), yet the relative importance of AOA and AOB to nitrification process in freshwater sediments remains under debate. Several previous studies indicated that AOA amoA gene abundance was usually greater than AOB in lake sediments (Herrmann et al 2009;Hou et al 2013;Zhao et al 2014), while the numerical dominance of AOB over AOA amoA gene abundance was observed in sediments of many freshwater lakes on the Yunnan Plateau (Liu et al 2015).…”
Section: Introductionmentioning
confidence: 99%